Stress hyperglycemia ratio predicts mid- to long-term mortality in first-hospitalized type 2 diabetes: Nonlinear threshold and prognostic value - Xiaohan Li; Radhakrishnan Muthukumar; Isaraporn Thepwongsa (PLoS ONE, 2026)
Background The stress hyperglycemia ratio (SHR) can more accurately reflect acute glycemic dysregulation by incorporating chronic glycemic levels. However, its association with mid- to long-term all-cause mortality in first-hospitalized patients with type 2 diabetes mellitus (T2DM), as well as its nonlinear characteristics, threshold effect and incremental predictive value, remain unclear. Methods This single-center retrospective cohort study enrolled 1,147 first-hospitalized T2DM patients. The prognostic value of SHR was evaluated using restricted cubic spline analysis, threshold effect analysis, Cox regression, subgroup analysis, sensitivity analysis and time-dependent receiver operating characteristic (ROC) curves. Results SHR was nonlinearly associated with all-cause mortality at all follow-up time points, with an optimal threshold of 1.08 (both P < 0.05). Each 0.1-unit increase in SHR was associated with a 10% higher risk of 3-year and 5-year mortality (HR = 1.10). SHR ≥ 1.08 was associated with increased risks of 3-year and 5-year mortality (HR = 2.38 and 2.28, both P < 0.001). Sensitivity analysis confirmed the robustness of results. Subgroup analysis showed that myocardial infarction, congestive heart failure and cerebrovascular disease significantly modified the prognostic effect of SHR. Time-dependent ROC demonstrated favorable predictive performance with AUC > 0.80 at all time points. Moreover, SHR resulted in modest improvements in AUC (0.825 → 0.835; 0.813 → 0.823) and C-index (0.792 → 0.802), outperforming traditional glycemic indicators. Conclusion SHR is independently and nonlinearly associated with mid- to long-term all-cause mortality in first-hospitalized T2DM patients (threshold = 1.08), and may provide incremental prognostic information for risk stratification.